DISKRIMINASI NEGARA TERHADAP AGAMA DI INDONESIA, STUDI ATAS PERSOALAN POSISI HUKUM TOWANI TOLOTANG PASCA PENGAKUAN AGAMA RESMI - Hasse J. Hasse J. (Universitas Gadjah Mada, 2011)
This paper aims to analyze the legal position of Towani Tolotang in the case of restrictions on religion in Indonesia. This paper is based on research toward the Towani Tolotang community in the Sidenreng Rappang Regency. Towani Tolotang is a local religion that continues to survive despite attempts to disband its followers, efforts which come not only from groups which disagree with the religion’s existence, but is also from the state. The discrimination experienced by followers of Towani Tolotang comes from two directions: first, from the public in the form of assumptions which denounce them, and second, from the government through a variety of regulations which limit the space for followers of Towani Tolotang to develop its teachings.